HADITH-BASED RELIGIOUS MODERATION: Strategies for Building Social Resilience among Indonesian Students in Syria in the Wake of the Fall of the Assad Regime - Nasrulloh, Nasrulloh; Munawwar, Faishal Agil; Harris, Abdul; Fahrudin, Ali; Umam, Khairul; Amri, Naufal Nuzulul (LP2M Ma'had Aly Hasyim Asy'ari Pesantren Tebuireng, 2025)
This study explores the role of hadith-based religious moderation in enhancing the social resilience of Indonesian students studying in Syria during the downfall of the Bashar al-Assad regime. The main objective is to identify strategies for implementing the values of religious moderation that are relevant to preventing radicalism and fostering social resilience. The research employs Yūsuf al-Qaraḍāwī’s theory of religious moderation within a sociological case study approach. Data were collected through in-depth interviews, non-participant observation, and documentation. The research questions include:(1) How is the contextual interpretation of ḥadīths on moderation understood among Indonesian students in Syria? (2) How are the prophetic principles of moderation applied to build social resilience in the post-Assad context? (3) What are the outcomes of internalizing hadith-based moderation among these students?The findings reveal that, based on al-Qaraḍāwī’s pillars of moderation, students demonstrate balance (tawāzun) by maintaining religious commitment while avoiding conflict and focusing on academic and religious studies. In terms of tolerance (tasāmuḥ), students show greater openness toward differences. Meanwhile, regarding comprehensiveness (syumūliyah),they actively engage in social interactions and embrace diverse groups without aligning with political factions. Social resilience efforts are manifested through hadith-based study circles emphasizing peace and harmony among Muslims. Consequently, Indonesian students remain unaffected by the demonstrations and civil resistance against the government.[Penelitian ini mengeksplorasi peran moderasi beragama yang berpijak pada hadis dalam meningkatkan resiliensi sosial mahasiswa Indonesia yang sedang studi di Suriah pada fase jatuhnya rezim Bashar Assad. Kajian utama bertujuan mengidentifikasi strategi implementasi nilai-nilai moderasi beragama yang relevan untuk mencegah radikalisme dan membentuk ketahanan sosial. Metodologi penelitian menggunakan teori moderasi beragama Yūsuf al-Qaraḍāwī dengan pendekatan studi kasus sosiologis. Pengumpulan data dilakukan melalui wawancara mendalam, observasi non partisipasi, dan dokumentasi. Rumusan masalah penelitian meliputi: (1) Bagaimana kontekstualitas interpretasi hadis-hadis moderasi di kalangan mahasiswa di Suriah? (2) Bagaimana implementasi hadis moderasi dalam membangun resiliensi sosial pasca-jatuhnya rezim Assad? (3) Bagiamana hasil internalisasi hadis moderasi bagi mahasiswa Indonesia di Suriah? Hasil penelitian menunjukkan bahwa berdasarkan pilar moderasi yang ditawarkan al-Qaraḍāwī, dari aspek tawāzun, mahasiswa mampu bersikap religius dengan menghindari konflik dan focus pada kajian ilmiah dan keagamaan. Dari aspek tasāmuḥ, mahasisa lebih toleransi dalam melihat perbedaan. Sementara dari aspek syumūliyah, mahasiswa aktif sosialisasi dan merangkul semua golongan tanpa terlibat dalam arus pro-kontra pemerintahan. Upaya resiliensi sosial diimplementasikan melalui kajian-kajian hadis moderasi yang mengedepankan perdamaian antar sesama muslim. Hal ini menjadikan mahasiswa Indonesia tidak terpengaruh oleh demonstrasi dan perlawanan rakyat terhadap pemerintah.]